Diffraction post-processor for polycrystalline plasticity modelling - Dini, D; Korsunsky, A; Dunne, F (2006)
Microscopic and macroscopic deformation of a polycrystal due to an applied load can be modelled using crystal plasticity implemented within the Finite Element (FE) framework. However, while macroscopic predictions can readily be validated against conventional monotonic and cyclic stress-strain curves, verification at the microscopic level is harder to achieve, since it involves calibrating the predictions for stresses and strains in individual grains, or in grains grouped by certain criteria (e.g., orientation). In this paper an elasto-plastic polycrystal finite element model is introduced, and its calibration is performed at a mesoscopic level via comparison with neutron diffraction data obtained experimentally. Time-of-flight (TOF) neutron diffraction experiments carried out on ENGIN-X instrument at ISIS involved in situ loading of samples of C263 nickel-based superalloy. In order to compare the numerical predictions of the FE model with these experimental data, the corresponding mesoscale average elastic strains must be extracted from the results of the simulation by employing a 'diffraction post-processor'. This provides a much improved technique for the calibration of FE formulation and enhances the confidence in the model. The FE diffraction post-processing procedures are discussed in detail, and comparison between the model predictions and experimental data are presented.